Optimalisasi Manajemen Kesiswaan pada Masa Pandemi Covid-19 di MTs Nurul Iman Kenali Asam Atas Kota Jambi - Najmul Hayat; Sumirah; Fitri Haryanti (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2022)
This study aims to determine the Implementation of Student Management Implementation During the Covid-19 Pandemic at Mts Nurul Iman Kenali Asam Atas Jambi City. This research uses qualitative methods. By using data collection techniques in the form of observations, interviews, and documentation. The results of this study in terms of planning, organizing, and supervision have gone well, but in the aspect of implementing learning in students, especially in online learning during the Covid-19 pandemic, there are still many obstacles, namely not involving parents of students so that many students do not participate in these online learning activities because some of their parents do not have android cellphones and there are many obstacles also those who already have but do not have a learning quota.